Loyalty programs for the passenger transportation industry: a study of Zimbabwean Companies - Kautsiro , Farium; Awolusi, Prof. Olawumi D. (Journal of Education and Vocational Research, 2020)
The paper examined firstly whether companies in the passenger transportation industry have utilised loyalty programs and then ascertained how much value the companies have drawn from them in enhancing market share, operational efficiency and financial benefit. Specifically, the study assessed the influence of loyalty program on customer relationship management, operational efficiency and profitability. The research was undertaken on ten companies who have implemented some form of loyalty programs through applied research’s in-depth interviews with the top executives. The qualitative methodology was utilised to simplify and manage the collection of data without affecting the environment and context. Data collected were further analysed via Chi-square statistics and the three hypotheses were tested at 5% level of significance. The results indicate that companies have begun to utilise loyalty programs in their operations, though not entirely sweating the programs to attain the best possible value from them. Most importantly, the study concluded on the positive significant relationship between loyalty program and customer relationship management, operational efficiency and profitability in the Zimbabwe loyalty program. Both filled a few highlighted gaps in the literature. Research for the road passenger transportation sub-sector offers useful theoretical and managerial implications as few studies have been conducted for the airline industry, which has successfully implemented loyalty programs through frequent flier schemes. It is recommended that companies should ascertain passenger behaviour through passenger registration, thereby enhancing the sustainability of the relationship. This study provides theoretical support for the importance of loyalty programs as passenger relationship management tools if appropriately applied and implemented. Loyalty programs offer companies across industrial sectors with useful benefits such as brand loyalty, business efficiency due to enhanced planning and profitability due to increase in patronage from passengers who are less sensitive to the marketing efforts of competing brands. This knowledge should, therefore, enable transporters to ascertain the value of adopting and using loyalty programs appropriately thereby enhancing their competitive advantage in a fast-paced world economy.